2023
DOI: 10.3390/catal13020411
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sonophotocatalytic Degradation of Acid Red 14 Using Fe3O4@SiO2/PAEDTC@MIL-101 (Fe) Based on Metal-Organic Framework

Abstract: Here, the magnetic Fe3O4@SiO2/PAEDTC@MIL-101 (Fe) with a new core-shell structure was synthesized, and its sonophotocatalytic properties were evaluated for acid red 14 (AR14) degradation. Particle characterizations were determined by scanning electron microscope (SEM), transmission electron microscopy (TEM), X-ray powder diffraction (XRD), and vibrating-sample magnetometer (VSM), and the analysis results offered an excellent synthesis of mesoporous particles. Fe3O4@SiO2/PAEDTC@MIL-101 (Fe)/UV/US showed high de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…In recent years, the high demand for modern technologies has led to water contamination by various pollutants, including toxic organic dyes and microorganisms. Organic dyes are classified into three types: cellulose fiber dyes (direct, sulfur, and indigo dyes), protein fiber dyes (azo, anthraquinone, triarylmethane, and phthalocyanine dyes), and synthetic fiber dyes (disperse and basic dyes). These dyes are used in various industrial, medical, and biological applications, such as printing, staining, food, textile, paper, drug production, and painting. However, releasing the aqueous industrial waste of these toxic dyes into natural water resources without pretreatment poses a significant threat to the environment and ecosystem. Such contamination can alter the properties of the soil, which threatens the fauna and flora in the vicinity, in addition to causing the death of microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the high demand for modern technologies has led to water contamination by various pollutants, including toxic organic dyes and microorganisms. Organic dyes are classified into three types: cellulose fiber dyes (direct, sulfur, and indigo dyes), protein fiber dyes (azo, anthraquinone, triarylmethane, and phthalocyanine dyes), and synthetic fiber dyes (disperse and basic dyes). These dyes are used in various industrial, medical, and biological applications, such as printing, staining, food, textile, paper, drug production, and painting. However, releasing the aqueous industrial waste of these toxic dyes into natural water resources without pretreatment poses a significant threat to the environment and ecosystem. Such contamination can alter the properties of the soil, which threatens the fauna and flora in the vicinity, in addition to causing the death of microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…This event demonstrates that O 2 molecules were converted into an O 2 •- reaction solution, decreasing the effectiveness from one hundred percent to 66.7% 48 . These findings indicate that the sonophotocatalytic process generates •OH, h + , and O 2 •- in the reaction solution 49 . A potential degradation mechanism for the sonophotocatalytic process has been postulated based on the results of the entrapment test and previous research 6 .…”
Section: Resultsmentioning
confidence: 64%
“… Al-Hawary et al (2023) depicted the mechanism of sonophotocatalytic treatment of dyes, using acid red 14 (AR14) as a model pollutant as shown in Figure 5 . They reported that the AR14 dye removal can be achieved in solution and catalyst surface through sonolysis and sonocatalytic processes.…”
Section: Water and Wastewater Treatment Applicationsmentioning
confidence: 99%